Carolacton Treatment Causes Delocalization of the Cell Division Proteins PknB and DivIVa in Streptococcus mutans in vivo - Reck, Michael; Wagner-Döbler, Irene (Frontiers in Microbiology, 2016)
The small inhibitory molecule Carolacton has been shown to cause chain formation and bulging in Streptococci, suggesting a defect in cell division, but it is not known how cell division is impaired on a molecular level. Fluorescent fusion proteins have successfully been applied to visualize protein localization and dynamics in vivo and have revolutionized our understanding of cell wall growth, cell division, chromosome replication and segregation. However, in Streptococci the required vectors are largely lacking. We constructed vectors for chromosomal integration and inducible expression of fluorescent fusion proteins based on GFP+ in S. mutans. Their applicability was verified using four proteins with known localization in the cell. We then determined the effect of Carolacton on the subcellular localization of GFP+ fusions of the cell division protein DivIVa and the serine-threonine protein kinase PknB. Carolacton caused a significant delocalization of these proteins from midcell, in accordance with a previous study demonstrating the Carolacton insensitive phenotype of a pknB deletion strain. Carolacton treated cells displayed an elongated phenotype, increased septum formation and a severe defect in daughter cell separation. GFP+ fusions of two hypothetical proteins (SMU_503 and SMU_609), that had previously been shown to be the most strongly upregulated genes after Carolacton treatment, were found to be localized at the septum in midcell, indicating their role in cell division. These findings highlight the importance of PknB as a key regulator of cell division in streptococci and indicate a profound impact of Carolacton on the coordination between peripheral and septal cell wall growth. The established vector system represents a novel tool to study essential steps of cellular metabolism.